Energy calibration and full-pattern refinement for strain analysis using energy-dispersive and monochromatic X-ray diffraction - Liu, J; Kim, K; Golshan, M; Laundy, D; Korsunsky, A (Wiley-Blackwell, 2005)
Precise channel-to-energy conversion is very important in full-pattern refinement in energy-dispersive X-ray diffraction. Careful examination shows that the channel-to-energy conversion is not entirely linear, which presents an obstacle to obtaining accurate quantitative data for lattice strains by pattern refinement. In order to establish an accurate quadratic channel-to-energy conversion function, a Matlab program was written to find the best quadratic coefficient and hence the whole energy conversion function. Then this energy conversion function was used to perform a whole-pattern fitting of the energy-dispersive X-ray diffraction pattern of a Ti64 sample. The strain across the Ti64 bar calculated from the fitting results has been compared with values obtained by single-wavelength X-ray diffraction utilizing a Laue monochromator. © 2005 International Union of Crystallography.